2024
DOI: 10.11591/ijece.v14i1.pp1005-1014
|View full text |Cite
|
Sign up to set email alerts
|

Real-time mask-wearing detection in video streams using deep convolutional neural networks for face recognition

Suhirman Suhirman,
Shoffan Saifullah,
Ahmad Tri Hidayat
et al.

Abstract: This research aims to develop a real-time mask-wearing detection system using deep convolutional neural networks (CNNs). This is crucial in the coronavirus disease 2019 (COVID-19) pandemic to alert individuals who are not wearing masks early on, thereby reducing the spread of the virus. Since COVID-19 primarily spreads through respiratory droplets and mask-wearing is recommended, our proposed study utilizes computer vision techniques, specifically image processing, to detect masked and unmasked faces. We emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…These CNNs have demonstrated successful applications in various deeplearning tasks, particularly in predicting and diagnosing colorectal cancer at an early stage. In this study, these CNN models have shown promising results and outperformed other approaches [7], [8].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…These CNNs have demonstrated successful applications in various deeplearning tasks, particularly in predicting and diagnosing colorectal cancer at an early stage. In this study, these CNN models have shown promising results and outperformed other approaches [7], [8].…”
Section: Introductionmentioning
confidence: 70%
“…Additionally, the confusion matrix components are employed to calculate important metrics like accuracy (ACC), precision positive predictive value (PPV), sensitivity (Recall), specificity (SPC), and F1-score. − Accuracy is the ratio of correctly predicted values to all predicted values, according to (7).…”
Section: Performance Evaluationmentioning
confidence: 99%